Preventing Conflicts Between Nurses and Families of a Multi-ethnic Patient Population During Critical Medical Situations in a Hospital. (May 2020) - Van Keer, Rose-Lima; Deschepper, Reginald; Huyghens, Luc; Bilsen, Johan
Introduction: Little is known about how to avoid intercultural nurse–family conflicts in critical care settings. In this article, strategies are discussed that may be useful to prevent or mitigate intercultural nurse–family conflicts during critical medical situations in hospital.Method: Strategies are based on an ethnographic study by Van Keer et al., other literature, and expert opinion.Results: Sufficient structural measures are needed. First, institutions must create appropriate ward policies, such as including nurses in end-of-life communication. Second, nurses should be coached in the workplace. Third, institutions must provide adapted, visual, ward information to families. Additionally, education and research are needed. These measures should be actively stimulated by nurse managers and reflect a multicultural program supported by the hospital.Discussion: Intercultural nurse– family conflict prevention or mitigation should take into account organizational aspects, on hospital units and in hospital as a whole, and the crucial role of education and research.